An overview of the tobacco problem in India - Gauravi A Mishra; Sharmila A Pimple; Surendra S Shastri (Indian Journal of Medical and Paediatric Oncology)
This is a review paper comprehensively encompassing the different aspects of tobacco control with particular reference to the Indian scenario. The information on prevalent tobacco habits in India, health hazards and environmental hazards due to tobacco use, passive smoking and its impact, economics of tobacco, legislation to control tobacco in India, the tobacco cessation services and the way ahead for effective tobacco control are discussed. Tobacco is a leading preventable cause of death, killing nearly six million people worldwide each year. Reversing this entirely preventable manmade epidemic should be our top priority. This global tobacco epidemic kills more people than tuberculosis, HIV/AIDS and malaria combined. This epidemic can be resolved by becoming aware of the devastating effects of tobacco, learning about the proven effective tobacco control measures, national programmes and legislation prevailing in the home country and then engaging completely to halt the epidemic to move toward a tobacco-free world. India is the second largest consumer of tobacco globally, and accounts for approximately one-sixth of the world′s tobacco-related deaths. The tobacco problem in India is peculiar, with consumption of variety of smokeless and smoking forms. Understanding the tobacco problem in India, focusing more efforts on what works and investigating the impact of sociocultural diversity and cost-effectiveness of various modalities of tobacco control should be our priority.